On the vibration of the block base under many parallel plane mechanisms - Khang, Nguyen Van (Vietnam Journal of Mechanics, 1992)
In this paper the vibration equations of the block base under many parallel plane mechanisms were established. Using the Taylor's formula and neglecting the nonlinear terms we obtain the linear vibration equations having periodic coefficients. There equations can be solved by numerical method using digital computer.